Constrained versus unconstrained rational inattention - Yaron Azrieli (Games, 2021)
The rational inattention literature is split between two versions of the model: in one, mutual information of states and signals are bounded by a hard constraint, while, in the other, it appears as an additive term in the decision maker's utility function. The resulting constrained and unconstrained maximization problems are closely related, but, nevertheless, their solutions differ in certain aspects. In particular, movements in the decision maker's prior belief and utility function lead to opposite comparative statics conclusions.
Keywords: 330; costly information; rational inattention; Shannon entropy